Risk Factors for Physical Function Impairments in Postintensive Care Syndrome: A Scoping Review - Ding, Min; Yang, Chunfeng; Li, Yumei (Frontiers in Pediatrics, 2022)
Objective: Survivors of critical illness may experience short- and long-term physical function impairment. This review aimed to identify the risk factors for physical function impairment from the current literature. Data Sources: A systematic search of the PubMed, Embase, Web of Science, and Cochrane Library databases following the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for Scoping Reviews guideline was performed. Study Selection: The risk factors reported in all human studies reporting physical function impairment in children admitted to the pediatric intensive care unit (PICU) were reviewed and categorized. Two investigators independently screened, evaluated, and selected studies for inclusion. Data from eligible studies were extracted by one investigator, and another investigator reviewed and verified the data. A systematic narrative approach was employed to review and summarize the data. Results: A total of 264 studies were found to be eligible, with 19 studies meeting the inclusion criteria. Children admitted to the PICU experienced physical function impairment during their stay, which can last for years. The studies varied primarily in the measurement timing and tools used. The most frequently reported personal risk factors for physical function impairment were age, race or ethnicity, a pre-admission chronic condition, sex, disease severity, duration or the presence of mechanical ventilation, and admission diagnosis. Conclusions: Physical function impairment may be persistent in PICU survivors. To prevent these impairments in critically ill patients, pediatricians should pay attention to modifiable risk factors, such as the duration of mechanical ventilation. Future studies need to promote a combination of standardized measures for the detection and prevention of physical function impairment.